PERAN PENGELUARAN SEKTOR PENDIDKAN DAN SEKTOR KESEHATAN TERHADAP KEMISKINAN DI INDONESIA - Wardhana, Adhitya; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
Poverty is the main problem in welfare society, no exception in Indonesia. In Southeast Asian Countries also have the same poverty problem, Indonesia in ranking fourth from eight countries in Southeast Asian. Education and health is need attention for reduce poverty. Education expenditure and medical expenditure is high for increase development so as reduce poverty. Method in research use panel data with approach fixed effect. Result in research show medical expenditure and education expenditure take effect positif to poverty and no significant.Variable control such as economic growth take effect negatif and signifikan to reduce poverty. Moreover unemployment take effect positif and no significant to poverty.